No Evidence of “Weaponized Title IX” Here: An Empirical Assessment of Sexual Misconduct Reporting, Case Processing, and Outcomes - Richards, Tara N. (2019)
Little is known about actual incidents of gender-based violence reported by college students or the campus adjudication process or outcomes of reported cases. Data from Annual Security Reports (ASRs) and Title IX Coordinators was used to examine the context, processes, and outcomes of reported incidents of sexual misconduct (n=1,054) at Institutions of Higher Education (IHEs) in a Mid-Atlantic state. Results showed that ASRs undercounted incidents of sexual misconduct. Few incidents reported to Title IX Coordinators resulted in a formal Title IX complaint, and fewer still resulted in a finding of responsibility or suspension/expulsion of the responsible student. The primary outcome of reports were victim services, not perpetrator punishments. Significant variability within and between IHE types was also uncovered. Findings suggest that better data collection as well as research on victim engagement in the Title IX complaint process and on sexual misconduct at Community Colleges and Independent IHEs is needed